FUNDS STATEMENT PRACTICES OF CERTIFIED PUBLIC ACCOUNTING FIRMS. - Kempner, Jack J. (The Accounting Review, 1957)
Perhaps the eventual growth in funds statement usage was inevitable due to the discrepancy that often exists between reported profits and available funds and to the recognition that working capital is the circulatory system of a business organization, with its preservation a primary concern to management. No amount of analysis of the income statement will signal approaching difficulty, although comparative balance sheets, if reviewed carefully, will reveal a diminishing supply of working funds. The location of the funds statement in published corporate annual reports varies from its inclusion with the primary financial statements to its appearance anywhere in the president's letter. Since audit reports are almost never published, accounting firms were requested to indicate the status they gave the statement in their long-form reports. It was probably very difficult for many accounting firms to determine, even approximately, the proportion of their clients which prepared their own statements. Distinguishing between cash and funds appears to cause the greatest amount of difficulty and it is in this area that more education is probably needed.